DAUR AL-MAR ATI FI NAJAH AL-HIJRATI FI AL-'AHDI AL-NABAWI - Fajar Tresna Utama (Jurnal Pemikiran Islam, 2021)
Since the revelation was revealed to our Prophet Muhammad, may God bless him and grant him peace, for the first time in the cave of Hira. The woman was not in isolation from the Prophet, may God bless him and grant him peace, and she was not excluded throughout the bright Islamic history from the initiative or participating in the da'wah march with all its events, and if we follow the role of women from the beginning of the revelation, we glimpse it clearly and without ambiguity. Prominent and without illusions, he, may God bless him and grant him peace, returned from the cave of Hira, afraid of what he saw. She patted his shoulder, and looked forward to the good from what he saw, so that he relieved his fear of security and tranquility, seeking with her cousin - Waraqah ibn Nawfal - to trust her husband from what he saw and increase him confidence and assurance, and by that she would be the first person to unite God after Muhammad (peace and blessings be upon him). She then takes the burden of the message in a way the history of a woman had never known before. These and other reasons preferred to write about a topic related to migration, which is: (The role of women in the success of migration during the Prophet's era). And this research also dealt with the definition of migration and the statement of the role of women in all stages of the prophetic migration and a conclusion and finally the researcher installed the list of sources and references. And one of the most important results is that the role of women is very great in emigration during the Prophet's era, since the revelation was revealed to the continuation of the call to the message. One of the most important recommendations is to pay attention to and care for the biography of the Prophet, and work to purify the biography books and Islamic culture from false narratives.